Publications Received (Academy of Management Review, 1987)
The article presents a list of publications received, including: "Bhopal: Anatomy of a Crisis," by Paul Shrivastava, "Business Not as Usual," by Ian I. Mitroff, and "The Business of Public Relations," by E. W. Brody.